Millennials tourism; Airbnb and the collaborative economy - Fonseca Saldaña, Ricardo Rolando (2020)
Tourist travel has changed in recent years; technological progress drives competitiveness and initiates business models, platforms and exchanges known as the collaborative economy. Airbnb web platform preferred by users who want to rent a space for travelers seeking accommodation because of the price flexibility compared to hotels; business that increases despite the distrust of hosting strangers. The Millennials constitute the new travellers, looking for new experiences, spaces with connections, respond to changes with economic options of premises with shared spaces in a responsible way; developing the healthy local economy benefits businesses that derive from tourism. They plan their trips by mobile devices, mix business and leisure tours related to adventure and nature, giving importance to comments on social networks.